(untitled) (Nordic Journal of Practical Theology, 2026)
The question this article seeks to answer: How do deacons in 2004 and 2015 describe and evaluate the activities of their local congregations and their own activities as diakonia? The data material is based on a survey among deacons conducted in 2015, which was a follow-up to a similar study conducted 10 years earlier. During this decade, many changes occurred that had an impact on the position of deacons. We have focused on three thematic areas: the activities of deacons, the cooperative relationships of deacons, and a factor analysis has been used to identify four deacon profiles. The profiles show systematic differences in the deacons’ assessment of what are important activities in local diakonia. The surveys are also seen in light of recent empirical research on the activities of deacons. Carlos Ham has outlined a (desired) development from charity (caritative diakonia), to community oriented diakonia that strives for reciprocity, and then on to transformative diakonia, and the results